Emotional Connection and Market Innovation: The Key Success Factors of Jellycat in the Chinese Market - Wang, Xinai (Transactions on Economics, Business and Management Research, 2024)
This paper examines the success factors of Jellycat in the Chinese market, focusing on the interplay of emotional marketing, hunger marketing, and diversified marketing channels. As modern life accelerates, consumers, particularly the younger generation, face significant pressure and loneliness, creating a heightened demand for emotional comfort. Jellycat has effectively established deep emotional connections with consumers through unique product designs, transforming plush toys into emotional companions. The hunger marketing strategy has created a sense of scarcity and a high-end image, further enhancing brand appeal. Additionally, diversified marketing channels have allowed Jellycat to reach a broader audience, maximizing its market impact. The findings suggest that Jellycat's approach is not only effective but also offers valuable insights for similar brands. For sustainable growth, Jellycat must continue to innovate in emotional value and integrate corporate social responsibility (CSR) into its business practices. By doing so, it can strengthen its market position and ensure long-term success.